What are they talking about when they talk about equity? A content analysis of equity principles and provisions in state Every Student Succeeds Act plans - Yiting Chu (Arizona State University, 2019)
Despite numerous education reform efforts, disparities between more privileged students and students from marginalized and minoritized groups still persist in U.S. education. The Every Student Succeeds Act (ESSA) passed in 2015 indicates greater commitment of the federal government to advancing equity in education and gives state educational agencies more autonomy and flexibility in policy making. This article analyzes the content of 52 approved state ESSA plans to examine how the concept of equity in education is defined and applied in state-level ESSA policies and provisions. Results of a qualitative content analysis reveal that all but four state ESSA plans adopt a stance on equity centered on equitable access to educational resources-including funding and effective educators -and less than half state plans attend to equity in outcomes. Most of the state plans do not include a clear definition of what they mean by "equity". In addition, the accountability systems used to evaluate the impact of equity policies in the plans are predominantly outcome-oriented using student standardized test performance as the key indicator. Incoherent policy principles, coupled with the market-oriented, standards-based policy solutions, may exacerbate the structural inequities facing schools and students that these policies aim to ameliorate. Implications for education policy and research are discussed.